Respon Masyarakat Lokal terhadap Pengembangan Kebun Raya Gianyar sebagai Destinasi Pariwisata di Desa Kerta - I Putu Ardita Yadnya; I Made Adikampana (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2019)
Gianyar Botanical Garden is one of the environmental conservation which will also be developed into a tourist destination in the village of Kerta. A tourist destination is a place that is owned, facilities, access and community related to him. The development of the Gianyar Botanical Garden as a tourist destination must have the authority, facilities, access and most importantly a positive response from the local community so that tourism in the Gianyar Botanical Garden can run well. Therefore, a research is needed to find out the community's response to the development of the Gianyar Botanical Garden as a tourism destination in Kerta Village. The method used techniques to analyze tourism product data in the Gianyar Botanical Garden and the local community response. Then used a method with descriptive statistical to analyze local community response data obtained through questionnaires. Data collection techniques using observation, interviews, questionnaires and literature studies. The informant determination technique uses purposive sampling. The technique of determining respondents uses the Slovin formula. To find out the local community response using the concept of local community response (Swastha and Handoko, 1997). The stages of developing the Gianyar Botanical Garden at the Involvement stage where tourism product development began to be carried out on attractions, facilities, access, marketing and planning. The response of the local community to the development of the Gianyar Botanical Garden as a tourism destination as a whole is very positive or Euphoria where local communities have welcomed the presence of tourism by giving them the trust and approval of community wishes fulfilled, information to local communities regarding the development of the Gianyar Botanical Garden and local communities participating voluntarily. Keywords : Local Community Response, Tourism Development.